SEROPREVALENCE OF HEPATITIS B AND C VIRUS IN VOLUNTARY BLOOD DONORS AT TERTIARY CARE HOSPITAL OF BANNU, PAKISTAN - Ullah, Mir Atta (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Background: After the introduction of blood banks, blood transfusion has become very common which can transmit many infections including hepatitis B and C viral infections. This study is aimed determine the seroprevalance of hepatitis B and C virus in voluntary un-paid blood donors and to make recommendations for safe blood transfusions. Methodology: This retrospective chart review study was conducted at Khalifa Gul Nawaz Teaching Hospital (KGNTH), Bannu, between 1st April 2011 and 31st March 2015. A total of 3650 voluntary blood donors were included in the study. All the blood samples were screened for hepatitis B surface antigen (HBSAg) and anti hepatitis C virus (AntiHCV) antibodies by enzyme linked immuno-sorbent assay (ELISA) before accepting the blood donation. Ages of donors ranged from 18-52 years. Males outnumbered the females. Results: Out of 3650 donors 61 (1.67%) were positive for HBSAg and 38 (1.04%) were positive for Anti-HCV. Conclusion: Although the seroprevalence of hepatitis B and C virus was low in this study but still it is of utmost importance to continue screening donated blood with highly sensitive and specific tests to ensure the safety of blood for recipient.